Lymphomatoid papulosis type A in a 7-year-old boy. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
Lymphomatoid papulosis is a papulo-nodular eruption, chronic and recurrent, actually included in the classification of primary cutaneous lymphomas. From a histological point of view, we distinguish a type A, which is reminiscent of Hodgkin’s lymphoma, a type B, which is reminiscent of mycosis fungoides and a type C, which is reminiscent of CD30+, anaplastic large cell lymphoma. About 60 cases of lymphomatoid papulosis were reported in children (1). In childhood the clinical course is chronic and recurrent for years, sometimes with complete regression. However, in some patients cases of lymphoma, also occurring in other organs (2), sometimes even 40 years after the onset of the cutaneous lesions, have been reported. Therefore, clinical and ultrasonographic prolonged monitoring of these children is mandatory.